Odpowiedź :
Odpowiedź:
Odp. A
Szczegółowe wyjaśnienie:
Ponieważ (-0,5) do potęgi -4 to 16 i podzielić do przez 1, ponieważ każda liczba do potęgi zero to 1 i podzielić na 8, wychodzi 2
Odpowiedź: A
Szczegółowe wyjaśnienie:
A.[tex](-0,5)^{-4}:\sqrt[3]{2}^{0} : 2x^{3} \\=0,5^{-4} : 1 : 2^{3}\\ =2^{4} :2^{3} \\=2[/tex]
B.[tex](\sqrt{10}+3\sqrt{4} )^{0} -1^{-1} \\= 1-1\\= 0[/tex]
C.[tex]\sqrt[3]{-27} : 3^{-2} \\=-3:3^{-2} \\=-3^{3}\\ =-27[/tex]
D.[tex]4\sqrt{3} - 2\sqrt{3}\\=(4-2)\sqrt{3}\\=2\sqrt{3}[/tex]